2012
DOI: 10.1073/pnas.1202509109
|View full text |Cite
|
Sign up to set email alerts
|

A molecular method for the delivery of small molecules and proteins across the cell wall of algae using molecular transporters

Abstract: Interest in algae has significantly accelerated with the increasing recognition of their potentially unique role in medical, materials, energy, bioremediation, and synthetic biological research. However, the introduction of tools to study, control, or expand the inner-workings of algae has lagged behind. Here we describe a general molecular method based on guanidinium-rich molecular transporters (GR-MoTrs) for bringing small and large cargos into algal cells. Significantly, this method is shown to work in wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…It has been reported that fluorescein-labeled octa-arginine (Fl-R8) can cross the cell wall of C. reinhardtii, algal cell uptake of Fl-R8 increases as the concentration of Fl-R8 increases, and a concentration of 50 μM is sufficient for strong internalization of F1-R8 [7]. It was also shown that Fl-R8 could enter different species of freshwater green algae but that cellular uptake was species specific.…”
Section: Translocations Of Fitc-r9 Into the Four Microalgal Speciesmentioning
confidence: 97%
See 3 more Smart Citations
“…It has been reported that fluorescein-labeled octa-arginine (Fl-R8) can cross the cell wall of C. reinhardtii, algal cell uptake of Fl-R8 increases as the concentration of Fl-R8 increases, and a concentration of 50 μM is sufficient for strong internalization of F1-R8 [7]. It was also shown that Fl-R8 could enter different species of freshwater green algae but that cellular uptake was species specific.…”
Section: Translocations Of Fitc-r9 Into the Four Microalgal Speciesmentioning
confidence: 97%
“…The translocation of CPPs into microalgae was performed following a previously described method with slight modifications [7]. FITC-R9 and free FITC were dissolved separately in phosphate buffered saline (PBS) to 50 μM.…”
Section: Cpp Translocationmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic modification is a crucial component for microalgal studies to understand and control the complex biological pathways, and realize higher photosynthetic efficiency, more consistent product quality, and higher resistance to pathogens [6,7]. However, the hard cell wall of the microalgae acts as a formidable barrier to the insertion (or delivery) of genetic materials [8].…”
Section: Introductionmentioning
confidence: 99%